2011
DOI: 10.1186/1824-7288-37-29
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical pattern of paediatric HIV infection at the University College Hospital, Ibadan, Nigeria: a prospective cross-sectional study

Abstract: BackgroundThe prevalence of Paediatric HIV infection is largely unknown in many countries in sub-Saharan Africa. This study was aimed at determining the prevalence, clinical pattern of HIV infection and outcome among new patients aged <15 years using age-specific diagnostic methods.MethodsA prospective cross sectional study was carried out using the provider initiated HIV testing and counselling (PITC) model. HIV rapid test in parallel was used for screening and confirmation was with HIV DNA PCR in children <1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
46
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 13 publications
14
46
5
1
Order By: Relevance
“…Two PHIV children in the current study had present otorrhea whereas no HIV-uninfected child presented with otorrhea. Statistics were not completed given the small numbers, though other researchers have shown that HIV-infected children in Africa have significantly more present or past episodes of otorrhea [7] and significantly more episodes of recurrent otorrhea [12].…”
Section: Discussionmentioning
confidence: 99%
“…Two PHIV children in the current study had present otorrhea whereas no HIV-uninfected child presented with otorrhea. Statistics were not completed given the small numbers, though other researchers have shown that HIV-infected children in Africa have significantly more present or past episodes of otorrhea [7] and significantly more episodes of recurrent otorrhea [12].…”
Section: Discussionmentioning
confidence: 99%
“…In all the studies analyzed, although they occurred in different regions and countries, oral manifestations were highlighted as a common feature in children infected with HIV virus. Most commonly found lesions were oral candidiasis in various forms 3 served in the analysis of Charts 1 to 4 and it will be further discussed in the course of this article.…”
Section: Leao Et Al 2009mentioning
confidence: 99%
“…The first three variants have been described as the types known to be associated with HIV infection nowadays 11 . Thus, it is possible to affirm that the opportunistic lesion most commonly associated with HIV-infected patients is oral candidiasis and that this finding is fundamental for the early diagnosis of AIDS [1][2][3]10,14,16,18,19 . In addition, this oral manifestation may serve as a marker of disease progression and immunosuppression 2,5,13,15 since its prevalence is related to lower values ofTCD4+ lymphocytes 1 .…”
Section: Meless Et Al 2014mentioning
confidence: 99%
See 2 more Smart Citations